Contribution of critical thinking, science process skills towards learning outcomes based on gender - Supratman Supratman; Siti Zubaidah; Muhammad Rafi’i Ma’arif Tarigan; Suhartini Azis (International Journal of Evaluation and Research in Education (IJERE), 2023)
The purpose of this study is to ascertain importance of scientific reasoning and process abilities to students’ learning outcomes based on gender differences. This type of research uses the kind of correlation research. This research was carried out for one semester a sample of 104 students studying biology in senior high schools in Sumbawa, Indonesia, with a total of 55 female and 49 male students. In this study, multiple-choice examinations were used to assess the students’ science process skills as well as their critical thinking abilities and learning outcomes. The findings the results of the multiple regression analysis demonstrate that the scientific method and critical thinking abilities are strongly correlated effectively children learn, depending on the gender difference. The importance of critical thinking abilities’ positive effects on learning outcomes of the female students was 81.60% and towards the learning results of the male students was 59.1. The usefulness of the science process skill in terms of practical contribution variable towards the learning results of the female students was 4.5%, and the male students were 20.6%. This means that the average simultaneous is classified as high. However, science process skills’ contribution to learning results is relatively low. The research finding shows that the science process skills have a low effective contribution towards students’ learning results based on gender differences, needs to be a serious concern. That is, implementing the appropriate learning models to enhance the development of science process abilities.